2015
DOI: 10.1007/s12012-015-9331-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-Specific Knockout of ETA Receptor Mitigates Paraquat-Induced Cardiac Contractile Dysfunction

Abstract: Paraquat (1,1'-dim ethyl-4-4'-bipyridinium dichloride), a highly toxic quaternary ammonium herbicide widely used in agriculture, exerts potent toxic prooxidant effects resulting in multi-organ failure including the lung and heart although the underlying mechanism remains elusive. Recent evidence suggests possible involvement of endothelin system in paraquat-induced acute lung injury. This study was designed to examine the role of endothelin receptor A (ETA) in paraquat-induced cardiac contractile and mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…To evaluate the proteomic responses to elevated oxidative stress, we first administered various doses of paraquat to C57BL/6J mice for 24 h. The animals (n = 4 per group) were exposed to three doses of paraquat (low—10 mg/kg; moderate—50 mg/kg; and high—75 mg/kg). The doses were chosen from a range previously reported for cardiac research models in the literature, with reports showing that exposure at 40–80 mg/kg for up to 48 hours induced acute oxidative stress responses as well as reduced contractile function and calcium handling in the mouse heart 15 , 18 , 21 23 . We first compared whether the applied paraquat doses elevated protein abundance of previously documented paraquat induced genes in the heart using mass spectrometry (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the proteomic responses to elevated oxidative stress, we first administered various doses of paraquat to C57BL/6J mice for 24 h. The animals (n = 4 per group) were exposed to three doses of paraquat (low—10 mg/kg; moderate—50 mg/kg; and high—75 mg/kg). The doses were chosen from a range previously reported for cardiac research models in the literature, with reports showing that exposure at 40–80 mg/kg for up to 48 hours induced acute oxidative stress responses as well as reduced contractile function and calcium handling in the mouse heart 15 , 18 , 21 23 . We first compared whether the applied paraquat doses elevated protein abundance of previously documented paraquat induced genes in the heart using mass spectrometry (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, chronic environmental exposure to residues of paraquat used as pesticide has been linked to the development of Parkinson′s disease 12 , whereas in rare cases acute paraquat poisoning at higher dose has also been reported that leads to significant multi-organ toxicity and mortality 13 , 14 . In laboratory experiments, high doses of paraquat ( 20–80 mg/kg) have been broadly used as in rodents to reliably induce acute oxidative stress in the heart 15 18 and in the lung 19 , 20 . In this study, we compared normal and acute paraquat-stressed mouse hearts using quantitative mass spectrometry, with the goal of assessing the effect of acute oxidative damage on the cardiac proteome.…”
Section: Introductionmentioning
confidence: 99%
“…The animals (n=4 per group) were exposed to three doses of paraquat (low -10 mg/kg; moderate -50 mg/kg; and high -75 mg/kg). The doses were chosen from a range previously reported for cardiac research models in the literature, with reports showing that exposure at 40-80 mg/kg for up to 48 hours induced acute oxidative stress responses as well as reduced contractile function and calcium handling in the mouse heart [13,[15][16][17][18]. We first compared whether the applied paraquat doses elevated protein abundance of previously documented paraquat induced genes in the heart using mass spectrometry (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…All mice were housed under well‐controlled conditions of temperature (22 ± 2°C), humidity (55 ± 5%) and a 12 h/12 h light‐dark cycle with access to food and water ad libitum . Four‐month‐old adult male TLR4 −/− and their age‐matched WT mice were delivered a single intraperitoneal injection of paraquat (45mg/kg, ∼100 μL, paraquat dichloride, Sigma‐Aldrich, St. Louis, MO) or the vehicle saline, and were examined 48 h later (Ge et al, ; Wang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The paraquat chemical shares close structural similarity with the dopaminergic neurotoxin 1-methyl-4-phenyl-pyridine to prompt the onset of Parkinson's disease (McCormack et al, 2002;de Oliveira et al, 2015). In addition, paraquat exposure may also result in detrimental sequelae in the heart and lung (Chan et al, 2007;Wang et al, 2014;Qian et al, 2015;Wang et al, 2016;Xu et al, 2015;Qiaoli et al, 2016). In particular, paraquat impairs myocardial contractile function and survival (Chan et al, 2007;Ge et al, 2010;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%